Cowboying for coexistence? Range riding in the New West - Smith, Ada P.; Martin, Jeff Vance; Kwait, Taylor; Anderson, Robert M.; Epstein, Kathleen; Charnley, Susan; Gosnell, Hannah (Frontiers in Conservation Science, 2025)
As wolf and grizzly bear populations recover across the American West, livestock producers face renewed challenges of coexistence, prompting increased interest in nonlethal conflict mitigation strategies. One such tool – range riding – uses human presence to prevent depredation and monitor livestock. While range riding is gaining traction among conservation practitioners and producers alike, empirical research on its implementation, effectiveness, and sustainability remains limited. This study examines range riding in the context of the “New West,” focusing on three long-standing programs in western Montana. Through semi-structured interviews with range riders and program coordinators (n= 7) supplemented by document analysis and broader research within the region, we explore how range riding is defined and practiced, its perceived benefits and challenges, and the labor and funding structures that support it. We find that range riding is understood as a flexible and context-specific form of human presence on the landscape, combining elements of predator deterrence, livestock monitoring, and grazing management, while facilitating producer compensation for livestock losses and relationship-building in rural communities. Interviewees described diverse benefits of range riding, including reduced livestock losses, improved communication between riders and ranchers/landowners, and its role in helping sustain working landscapes amid broader socio-economic shifts. However, programs face significant challenges: limited long-term funding, high labor demands, and difficulties in hiring and retaining skilled riders capable of building trust with ranchers and the broader community. Ironically, the success of range riding in reducing depredation can jeopardize its continued funding – a dynamic we term the “paradox of prevention.” Our findings suggest that range riding represents a return to traditional rangeland practices – “cowboying” – amid novel political and economic circumstances. As such, its future depends on durable funding, supportive policy frameworks, and recognition of its role in shaping coexistence between predators and people in the New West.